INTEGRATION OF VALUES EDUCATION IN LEARNING ISLAMIC RELIGIOUS EDUCATION: BUILDING STUDENTS' MORAL DEVELOPMENT - Arman Paramansyah; Wulandari; Muhajir Musa; Syatria Adymas Pranajaya (Adisam Publisher, 2024)
Values education is a process of guidance through role models. Education that is oriented towards instilling life values which include religious, cultural, ethical and aesthetic values towards the formation of students who have religious spiritual intelligence, self-control, complete personality, morals. noble, as well as the skills needed by himself, society and the country. The content of educational values is all vague and too western-flavored. Recently there has been talk about the Islamicization of science. In this sense it can be said that the Islamization of science is an alternative-strategic solution. This effort is encouraging if technical and non-technical factors contribute to fertilizing the climate. However, if it is only euphoric, it would be very regrettable. Instead of looking for a strategic alternative solution, in fact it could be a strategic alternative solution for certain groups who only seek to profit from public opinion, which has great potential because the majority of the population is Muslim. In evaluating the value education integration process, you can use the 5P assessment technique (paper and pencils, portfolio, project, product, and performance). This 5P assessment is directed at the context of value education in the family, school and society.